Gambaran karakteristik pasien kista ovarium jinak yang dilakukan tindakan operasi di Bagian Ginekologi di RSUP H. Adam Malik medan periode 1Januari 2009 - 31 Desember 2013 - Ninong Ade Putri; Aswar Aboet; M Oky Prabudi; Deri Edianto; Sarma Lumbanaja; David Luther (Fakultas Kedokteran USU, 2014)
Introduction : Ovarian cyst is a benign tumor with liquid content. This is often found in women in their reproductive periods. Knowing the epidemiology of ovarian cysts is important for all aspects of health. Analyzing patients’ charateristic who underwent laparotomy or laparoscopic for ovarian cyst ovarian cysts will give us data about preferences of each method as a useful statistical data in the informed consent or determining therapy choice.Objective : To determine the characteristics of the ovarian cyst patient who underwent laparoscopy and laparotomy. Methods : This study is a retrospective descriptive study with cross sectional design using all patient medical records benign ovarian cysts who have undergone surgery in the Departemen of GynecologyinHaji Adam Malik Hospital from 1 January 200 to 31 December 2013. Parameters assessed were age, parity, tumor size, menstrual status, body mass index, in each surgical group. The data collected is presented in the form of tables and diagrams.Results :I n this study, 163 patients were included.Laparoscopy in benign ovarian cysts entirely (100%) is cystectomy and majority laparotomy method was SOU laparatomy (58.9%). Majority patients who undergo laparoscopy vslaparatomy, aged 21-35 vs. 36-50 years old (52.9% vs 30.82.6%), nulliparity versus multiparity (70.58% vs 30.8%), tumor size 5-10 cm vs>10 cm (88.23% vs 48.63%), both still menstruating (100% vs 56.16%), normoweightvs obese 1 (70.58% vs 30.8%). Conclusions : There are differences between the characteristics of the group who underwent laparoscopy and laparotomy.